Non-mega sporting events and urban development: Assessing the impact of the 2022 Mediterranean Games on the socio-urban development of Oran city - Bouadam Chaima; Lazri Youcef; Salah-Salah Hana (Glasnik Srpskog Geografskog Društva)
This article explores the Mediterranean Games as non-mega sporting events (NMSE), with a focus on their impact on urban development of host cities, in this case the city of Oran. It examines how the city leveraged the event for infrastructure, tourism and local economic growth. The initial hypothesis suggests that the Games acted as a catalyst for significant investments that promoted sustainable urban development. Through an exploratory analysis, the study investigates socio-spatial and territorial impact from the bid-ding phase to the post-event period. Findings reveal that, while not comparable in scale to the Olympics, the Mediterranean Games significantly influenced Oran’s urban and social development, generating major urban projects and encouraging international cooperation and cultural exchange among participating nations.